Preparation and characterisation of polymerisable bicontinuous microemulsion membranes for water treatment application - Galliano, Francesco; Bartolino, Roberto; Gabriele, Bartalo; Figoli, Alberto; Veltri, Lucia (My University, 2013)
Climate changes, population growth and urbanization are some of the causes of water shortage in many countries of the world. Water is essential to the life of all living organisms and its preservation and responsible use are some of the challenges that humanity will face in the near future. In particular, the possibility of treating and re-using municipal and industrial wastewaters can represent an important solution to water scarcity. Technological breakthroughs have led to the development of a number of technologies that can be efficiently applied in wastewater treatment. Among them, membrane applications are receiving an increasing attention thanks to their versatility, low environmental impact, easy scale-up and high product quality. Aim of this thesis was to produce polymeric membranes obtained through the polymerisation of a polymerisable bicontinuous microemulsion (PBM). Bicontinuous microemulsions consist of an interconnected network of oil and water channels stabilised by a surfactant. Oil channels can be polymerised, forming the membrane matrix, while water channels remain unaffected, forming the pores. In the present work, for the first time PBM membranes were applied, by polymerisation, as coating material for commercial polyether sulfone (PES) membranes. In the first part of the work, the polymerisable surfactant acryloyloxy undecyltriethylammonium bromide (AUTEAB) was synthesised and used for microemulsion formulation. The possibility of using a non-polymerisable surfactant such as dodecyltrimethylammonium bromide (DTAB) was also evaluated. In the second part of the work, novel membranes prepared by microemulsion polymerisation were characterised in order to select the proper membrane with suitable characteristics and properties. Characterization tests carried out on PBM membranes showed the great potential that these membranes could have on wastewater treatment in membrane bioreactor (MBR) applications. In particular, the very smooth surface, the relatively high hydrophilicity and the channel-like structure (typical of the bicontinuous microemulsion) make PBM membranes less prone and highly resistant to fouling. This aspect is the key point if we consider that fouling is one the major drawbacks affecting almost all membrane processes. Fouling is mainly due to the deposition of organic and/or inorganic matter on the surface of the membrane, causing therefore a decline in membrane performance, an increase in energy consumption and (in severe cases) damage of the membrane structure. Furthermore, PBM membranes, due to the presence of a cationic surfactant, present an interesting antimicrobial activity. The possibility of having membranes with antimicrobial properties prevents the phenomenon of biofouling caused by the adhesion and the accumulation of microorganisms at membrane surface. PBM coated membranes were, then, successfully applied to the MBR process for the treatment of wastewater from textile dying. PBM coated membranes, when compared with commercial PES membranes, showed superior results for a long time (6 months) in terms of permeability and dye rejection. Moreover, less cleaning efforts were required leading to lower costs. Novel PBM coated membranes developed can be, thus, also applied to other membrane processes for wastewater treatment.
Scuola di Dottorato in Scienza e Tecnica Bernardino Telesio, Organic Materials of Pharmaceutical interest XXVI Ciclo CHIM, a.a. 2012-2013
Keywords: Chimica organica; Membrane; Reazioni chimiche